NO2 Gas Sensing Properties of Ag-Functionalized Porous ZnO Sheets. (19th January 2023) - Kim, Min Young; Hwang, Jeong Yun; Mirzaei, Ali; Choi, Sun-Woo; Kim, Sang-il; Kim, Hyun-Sik; Kim, Sun-Jae; Roh, Jong Wook; Choi, Myung Sik; Lee, Kyu Hyoung; Lee, Seung Yong; Jin, Changhyun
Abstract : Herein, we report a simple and scalable synthesis route to prepare Ag-functionalized porous ZnO sheets and their enhanced NO2 gas sensing properties. Porous ZnO sheets functionalized with well-dispersed submicron Ag particles were prepared by using a hydrothermal method-based one-pot synthesis route from Zn and Ag precursors. NO2 gas sensing performance (response, selectivity, response time, and recovery time) was optimized at 200°C in the gas sensor fabricated with 3 at% Ag-functionalized porous ZnO sheets. We demonstrated a response (R g /R a ) of 17.18 to 10 ppm NO2 gas and also obtained a high response of 14.05 even at 60% relative humidity due to the synergetic effect of improved NO2 gas adsorption in the presence of Ag particles and increased resistance by the formation of Schottky barrier at Ag-ZnO heterojunctions.